FACTORS THAT INFLUENCE THE SMOKING BEHAVIOUR OF MALE STUDENTS IN DORMITORIES - Febrijanto, Yoyok; Fikriyah, Samrotul (Jurnal Penelitian STIKES Kediri, 2012)
Smoking behavior is behavior that harm to health, but many people still do it, even more people start smoking when he was a teenager. Although everyone knows about the dangers caused by smoking, but this has never ended and every moment can be found many people who were smoking and even more smoking behavior has been familiar among teenage boys. The use of substances becomes several factors for young person, so that they become smokers, such as psychological factors, biological factors and environmental factors. The design used in this research was analytic description. The population was male students who living in dormitories of Stikes RS Baptis Kediri who met the inclusion criteria. The samples were 33 respondents using total sampling. The independent variables were psychological factors, biological factors, environmental factors and the dependent variable was smoking behavior. The data were collected by questionnaire, and then analyzed using multiple linear regression statistical test with significance level Î± â‰¤ 0.05. The results of this researchshowed that less than 50% of respondents who had less risk of psychological factor and light smoking behavior was 11 respondents (33.3%). The result of statistical test with multiple linear regressions was p = 0.007,howas accepted and ha was rejected, which meant there was the influence of psychological factors on smoking behavior to male students in dormitory of Stikes RS Baptis Kediri. The conclusion of this research showed there was positive verificationÂ factors that influence smoking behavior to male students in dormitory of Stikes RS Baptis Kediri namely psychological factor.